Aortic pseudoaneurysm repair after Bentall procedure using the IntraClude device. Issue 12 (1st October 2020) - Mayr, Benedikt; Alalawi, Zahra; Ziegelmüller, Johannes A.; Nöbauer, Christian; Krane, Markus; Lange, Rüdiger; Voss, Bernhard
Abstract: Background: Despite advances in surgical techniques, aortic reoperation is still associated with a high risk of mortality due to possible injury of the myocardium or great vessels during resternotomy. Materials & Methods: We report the case of a giant aortic pseudoaneurysm, 17 years after the Bentall procedure in a 76‐year‐old male patient. Results: Successful pseudoaneurysm resection after the Bentall procedure using the ThruPort IntraClude intra‐aortic occlusion device (Edwards Lifesciences) was achieved. Discussion: The IntraClude catheter can be used effectively to provide endovascular clamping of the ascending aorta during challenging cardiac reoperations.